The Influence of Talent Management and Work Motivation on the Performance of Non-PNS Government Employees at Ganesha University of Education - MANUABA, Ida Bagus Ngurah Sidharta; RAHMAWATI, Putu Indah; SUARMANAYASA, I Nengah (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to examine the influence of talent management and work motivation on the performance of Non-PNS government employees at Ganesha University of Education. The research method used is a survey method using a questionnaire as a data collection tool. The research sample was Non-PNS government employees at Ganesha University of Education consisting of various work units. The object of the study involved employees divided into several departments totaling 136 respondents to be used as samples. The results of data analysis using multiple linear regression methods showed that talent management has a positive and significant influence on the performance of Non-PNS government employees at Ganesha University of Education. Likewise, work motivation has a positive and significant influence on the performance of Non-PNS government employees at Ganesha University of Education. The findings of this study indicate that talent management and work motivation play an important role in improving the performance of Non-PNS government employees at Ganesha University of Education. Therefore, improving talent management and work motivation can be an effective strategy for the government and educational institutions to improve the performance of Non-PNS government employees at Ganesha University of Education.